Biodegradation Kinetic Study of Cassava & Tannia Starch-Based Bioplastics as Green Material in Various Media - Marcelinus Christwardana; Ismojo Ismojo; Sidik Marsudi (Universitas Jenderal Soedirman, 2022)
The rate of biodegradation of cassava – tannia starch bioplastic in various media was evaluated. Bioplastic degradation profile for a period of 4 weeks was seen following the Hills Equation where the speed of bioplastic biodegradation in sand media had higher yields than farm soil and compost media with the value up to 98.84 %. This is also proven by measuring the rate of degradation reaction using a first order reaction rate, where the value of the constant rate of reaction from bioplastics in sand is a little bit higher compared to farm soil and compost media (0.77647, 0.67133, and 0.15779 week-1, respectively). According to SEM pictures, there were numerous bacteria (either aerobic or anaerobic) and fungal species on the bioplastic surface, which have a role in the biodegradability of the polymer in bioplastics. The FTIR spectra of bioplastic biodegradation showed a decrease in the peak at 3400 - 3200 cm-1, and loss of the peak was present in the control at 2900 cm-1 which showed a breakdown of the polymer chain in the bioplastic especially in the O-H and C-H bonds, respectively. It can be concluded that farm soil and sand are the most optimal media in the bioplastic biodegradation process, while compost has potential but its maturity must be considered.